A Copper‐Catalyzed Aerobic [1, 3]‐Nitrogen Shift through Nitrogen‐Radical 4‐exo‐trig Cyclization. (26th October 2017) - Li, Yan; Wang, Rui; Wang, Tao; Cheng, Xiu‐Fen; Zhou, Xin; Fei, Fan; Wang, Xi‐Sheng
Abstract: A novel radical [1, 3]‐nitrogen shift catalyzed by copper diacetate under an oxygen atmosphere (1 atm) has been developed for the construction of a diverse range of indole derivatives from α, α‐disubstituted benzylamine. In this reaction, oxygen was used as a clean terminal oxidant, and water was produced as the only by‐product. Five inert bonds were cleaved, and two C−N bonds and one C−C double bond were constructed in one pot during this transformation. This unique method demonstrated broad application protential for the late‐stage modification of biologically active natural products and drugs. Mechanistic investigations indicate that a unique 4‐ exo ‐trig cyclization of an aminyl radical onto a phenyl ring is involved in the catalytic cycle.